Aristotle and Heidegger concerning the apophantic function of λόγος - De Blassi, Fernando Martín (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2021)
This paper analyzes the existential interpretation of language that Heidegger develops in §34 of Being and Time. There, Heidegger shows the possibility of using the Greek term λόγος in order to signify the meaning of German word Rede. The examination refers a fortiori to a §7 B where the philosopher proposes, among other aspects, the translation of λόγος by “saying”, whose primary function is designated by the verb ἀποφαίνεσθαι. Heidegger appeals to the authority of Aristotle as a source that has thematized such “saying” as ἀπόφανσις. Consequently, the first chapters of De Interpretatione will be considered in order to recognize the limits and scope of the Heideggerian understanding regarding the definition that the Stagirite attributes to the concept of λόγος ἀποφαντικός.